2013
DOI: 10.1007/s12098-013-0985-z
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Childhood Obesity: Need for a Trans-Sectoral Convergent Approach

Abstract: The emerging burden of non communicable diseases is likely to erode the "Demographic-Dividend" of India and compromise the national growth and development. Increasing rates of childhood obesity globally and in India is a cause for serious public health concern. It is becoming increasingly apparent that obesity is result of complex interplay between multiple genes, environmental factors and human behavior. Clear comprehension of this interaction and pathway is still not clear, making the prevention and manageme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 54 publications
0
10
0
Order By: Relevance
“…All these changes influence the food system in ways that then fuel behavior changes linked with increased energy-dense food consumption and reduced physical activity [ 3 , 4 ]. In particular, living in an urban setting has been linked with increased risk of childhood obesity in developing countries [ 2 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…All these changes influence the food system in ways that then fuel behavior changes linked with increased energy-dense food consumption and reduced physical activity [ 3 , 4 ]. In particular, living in an urban setting has been linked with increased risk of childhood obesity in developing countries [ 2 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that economic changes and globalization have increased Indian children’s reliance on technology and interest in sedentary pursuits and that inadequate activity is contributing to rising obesity, particularly among affluent children (Kiranmala et al, 2013; Kotian et al, 2010). However, children in our study, who attended private school and were from relatively high-status families, indicated that being active was important to them.…”
Section: Discussionmentioning
confidence: 99%
“…Popkin and colleagues linked this nutrition transition to economic, technological, and social changes. At the same time, the transition to industrialized economies and expanding access to technology may be making many leisure, occupational, household, and transportation activities more sedentary (Gupta et al, 2012; Kiranmala et al, 2013). Behavior changes may also reflect changing preferences influenced by access to new goods and ideas through global markets and mass media (Sullivan et al, 2011; Verma and Sharma, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Hazreen et al, further reported high sedentary lifestyle among adolescents from rural area in Malaysia which may contribute to the occurrence of adiposity [4]. Numerous studies reported that physical activity was inversely correlated with obesity [5][6][7][8]. The knowledge regarding the relationship between physical activity and obesity was important in order to tackle the childhood obesity problem in Malaysia [9].…”
Section: Introductionmentioning
confidence: 99%